2019
DOI: 10.3389/fcell.2019.00094
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Functions of the Golgin Vesicle Tethering Proteins

Abstract: The golgins comprise a family of vesicle tethering proteins that act in a selective manner to tether transport vesicles at the Golgi apparatus. Tethering is followed by membrane fusion to complete the delivery of vesicle-bound cargo to the Golgi. Different golgins are localized to different regions of the Golgi, and their ability to selectively tether transport vesicles is important for the specificity of vesicle traffic in the secretory pathway. In recent years, our mechanistic understanding of golgin-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 101 publications
1
50
0
Order By: Relevance
“…To determine whether Golgi outposts function to create or maintain the dendrite-specific orientation of microtubules, we analyzed microtubule polarity in neurons in which we eliminated the cis-Golgi matrix protein GM130. GM130 has the potential to both recruit the protein machinery for MTOC activities (microtubule nucleation, anchoring, and stabilization) and contribute to forming multi-compartment Golgi units (Barr et al, 1997;Kondylis et al, 2005;Liu et al, 2017;Lowe, 2019;Martin and Akhmanova, 2018;Nakamura et al, 1995;Sanders and Kaverina, 2015;Zhou et al, 2014). We found that the percentage of multi-compartment outposts decreases when GM130 is absent, which supports the model that GM130 participates in connecting Golgi compartments in neurons ( Figure 1D) (Zhou et al, 2014).…”
Section: Removing Gm130 Reveals Golgi Outposts Are Not Essential To Tsupporting
confidence: 84%
See 1 more Smart Citation
“…To determine whether Golgi outposts function to create or maintain the dendrite-specific orientation of microtubules, we analyzed microtubule polarity in neurons in which we eliminated the cis-Golgi matrix protein GM130. GM130 has the potential to both recruit the protein machinery for MTOC activities (microtubule nucleation, anchoring, and stabilization) and contribute to forming multi-compartment Golgi units (Barr et al, 1997;Kondylis et al, 2005;Liu et al, 2017;Lowe, 2019;Martin and Akhmanova, 2018;Nakamura et al, 1995;Sanders and Kaverina, 2015;Zhou et al, 2014). We found that the percentage of multi-compartment outposts decreases when GM130 is absent, which supports the model that GM130 participates in connecting Golgi compartments in neurons ( Figure 1D) (Zhou et al, 2014).…”
Section: Removing Gm130 Reveals Golgi Outposts Are Not Essential To Tsupporting
confidence: 84%
“…We targeted the cis-Golgi matrix protein GM130, which has two key roles: first, work done in mammalian cells has shown that GM130 recruits AKAP450, which in turn recruits protein complexes that nucleate, tether, and stabilize microtubules (Hurtado et al, 2011;Rivero et al, 2009;Roubin et al, 2013;Wu and Akhmanova, 2017). Second, GM130 is needed for proper Golgi structure and connects Golgi compartments to form multi-compartment units, including outposts (Barr et al, 1997;Kondylis et al, 2005;Liu et al, 2017;Lowe, 2019;Nakamura et al, 1995;Zhou et al, 2014). Strikingly, we found that the global orientation of dendritic microtubules is unaffected by the loss of GM130 or the fly AKAP450 ortholog plp.…”
Section: Introductionmentioning
confidence: 99%
“…Coiled‐coil tethers, as their name suggests, consist of a long coiled‐coil structure often terminating with a noncoiled‐coil head domain, and, many if not all CCTs function as dimers . Most of the known CCTs reside at the Golgi and are often called Golgins . Although CCTs all have a similar structure, they vary greatly in size (from ~ 50 to ~ 400 kDa).…”
Section: Intracellular Membrane Trafficking Pathways and Machinerymentioning
confidence: 99%
“…Most vertebrate cells contain 100-200 stacks, each comprised of four to six cisternae (Storrie et al, 2012;Sin and Harrison, 2016). In addition, these stacked cisternae are laterally interconnected into a single, contiguous ribbon-like entity that is positioned next to the centrosomes in the perinuclear region (Lowe, 2019). By joining adjacent cisternae between stacks, the Golgi can accommodate and process large secretory cargos that do not fit into individual cisternae such as collagen or Weibel-Palade bodies (Ferraro et al, 2014;Lavieu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%